Pterygium extended removal followed by minor ipsilateral simple limbal epithelial transplantation (PERMISLET): An innovative technique for recurrent pterygium - Alok Sati; Sanjay Kumar Mishra; Sarvadarshi Shukla; Deepesh Unni; Sonali V. Kumar; Sanjay Kumar Dhar; Jaya Kaushik; Vijay Kumar Sharma; Anju Pannu (Indian Journal of Ophthalmology)
We describe a novel technique for recurrent pterygium and assess the advantage of properties of extended tenonectomy, amniotic membrane transplantation, and limbal epithelial transplantation in terms of recurrence rate, postoperative symptoms, postoperative orthoptics, and other complications. A total of nine eyes with recurrent pterygium underwent PERMISLET, i.e., pterygium extended removal (PER) (removal of tenon capsule with fibrovascular tissue around medial rectus from limbus till medial canthus) followed by minor ipsilateral limbal epithelial transplantation (coverage of bare sclera with amniotic membrane graft and placement of ipsilateral limbal pieces at the affected limbus). The patients were reviewed on day 1, day 7, and day 30 and at third, sixth, and twelfth month after surgery, and none of the eyes (0/9) showed recurrence of pterygium on to the cornea. Time taken for surgery was 53.88 ± 8.74 minutes (range, 45 to 75 minutes). Postoperative discomfort (pain, irritation, foreign body sensation, and lacrimation) persisted mainly for day 1 after the surgery. However, lacrimation persisted till day 7 in two of the patients. Intraoperative complications were seen in none of the eyes. A total of 1/9 patients had granuloma formation, and 1/9 had dellen formation in postoperative period with successful management. Moreover, none of the eyes (0/9) developed ocular motility restrictions in postoperative period. PERMISLET, an innovative surgical technique for recurrent pterygium, is a viable option with zero rate of recurrence and minimal complications, a boon for patients with limited healthy conjunctiva or a potential for future glaucoma drainage procedures.